Osteonecrosis of the jaw as a complication of a bisphosphonate therapy - Furman, Janusz; Sosnowska-Klocek, Edyta (Psychoonkologia, 2015)
A 53-year old woman with kidney cancer diagnosed 8 years ago who was treated with zoledronic acid due to bone metastases was depicted. Although bisphosphonate administration resulted in the reduction of pain and improvement in performance status the treatment was stopped due to osteonecrosis of the jaw that dramatically worsened patient’s quality of life: pain hindering food intake (weight loss) with uncontrolled hypersalivation, xerostomia and fetor ex ore. Treatment consisted of gabapentin and an anxiolytic, fentanyl 50 mcg/h patch was maintained, patient was consulted with a stomatologist who undertook local treatment with dressings with turpentine with metronidazole and solcoseryl prepared ex tempore, rinsing with hydrogen peroxide, coconut oil and Axerosta®, which relieved symptoms and almost complete eliminated fetor ex ore. Acupressure (auriculotherapy) was used with a very good result causing resolution of hyperalgesia and significant reduction of neuropathy in the jaw. The case indicates that bisphosphonate treatment should be carefully considered in every case and that patients require right preparation: curing teeth problems, complementation of calcium level, undertaking cooperation with experienced stomatology center for permanent monitoring of treatment.